Composition and distribution of earthworms in Luc Ngan district, Bac Giang province and potential using in anti erosion and in soil amelioration - Binh, Tran Thanh; Nhung, Tran Hong (Academia Journal of Biology, 2012)
A research on earthworms was carried out in Luc Ngan district, Bac Giang province during one year: 4/2007-4/2008. Quantitative and qualitative samples on earthworms were collected from six habitats: shrub hill, grass land, river-closed area, hilly soil with long-term trees, house garden and field dam. The research result showed that 33 earthworm species belonging to 8 genera, 6 families have been found in Luc Ngan district, Bac Giang province. Among them, Pheretima is the largest genus with 21 recorded species in comparison with total of 33 species. Especially, two species: Glyphidrilus papillatus (Microchaetidae) and Ramiella bishambari (Octochaetidae) are newly recorded to the Northeastern region of Vietnam. Based on the original distribution, earthworm species found in Luc Ngan belong to 4 groups: species from hilly area (11 species), from plain (7 species), from mountainous area (3 species) and widespread species (3 species) In other hand, all earthworms found in Luc Ngan are also classified into 3 different morpho-ecological groups based on both morphological and ecological characteristics: litter dwelling (2 species), litter-soil dwelling (15 species) and soil dwelling (15 species). The density, biomass, frequency of occurrence and ecological characteristics of earthworm were also analyzed in the paper. In total of 32 species, Pheretima robusta, Ph. aspergillum, Ph. morrisi and Ph. exillis are the most abundant species in research area. Based on this result, some criteria are proposed for selecting approximate species to prevent soil erosion and to ameliorate soil quality